The Use of Audio-Visual Materials in Teaching and Learning Process in Effia Junior High Schools - Kwegyiriba, Adwoa; Mensah, Ronald Osei; Ewusi, Elizabeth (Technium Social Sciences Journal, 2022)
This study aims to find out the use of audio-visual materials at the Junior High School level. Despite the fact that the use of audio-visual materials is a proper current technological tool to motivate students, it prevails a set of challenges in the availability of audio-visual materials in Effia public Junior High Schools. The study seeks to provide information on the existing situation about the availability and use of Audio-visual materials in teaching students in Junior High Schools in Effia, in Effia Kwesimintsim Municipal Assembly. This study used qualitative approach, and censused all the nine public Junior High schools in Effia with ten students and one teacher randomly selected from each public JHS in Effia to form a sample size of 99 respondents for the study. Despite the significant role played by the use of audio-visual materials in the Ghanaian educational system. The findings revealed that although the students in the nine public JHS in Effia are not taught using Audio-Visual materials by their teachers, they still have the desire to be taught using those materials and this was affirmed with a significant majority of the students saying they desired to be taught with Audio-Visual materials in their various classrooms experience. The research recommended that Audio-Visual materials should be made available by Stakeholders in the educational sector such as; the Parent Teacher Association (P.T.A), the municipal assembly, the ministry of education, the Ghana Education Service, individual philanthropists, and non-governmental organizations.